The Willingness of Farmers to Adopt Innovations from Farmer-Owned Enterprises (BUMP) - Wicaksono, Karuniawan Puji; Kusuma, Bayu Adi; Permanasari, Paramyta Nila; D.P, Della Aprillia; Dewi, Rahma Wilda Kusuma; Ramadhani, Mirza; Rohman, Ach. Ainur (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2024)
A Method to increase the capacity of farmers is through farmer institutions. BUMP or know as (Farmer-Owned Enterprise) is one of the farmer institutions which incorporate in the agricultural commodity association. BUMP is helpful association for increasing farmer’s income and knowledge, facilitating farmers in obtaining production facilities and also capital, and facilitating the sale of crops to increase the productivity of agricultural products. However, behind the benefits provided, there are challenges that must be faced related to the willingness of farmers to adopt innovations. This study pays attention to how the influence of self-efficacy and attitude on the willingness to adopt is supported by the variables Perceived Ease of Use and Perceived Usefulness. This research was conducted in Dadaplangu Village, Ponggok District, Blitar Regency. Respondents in the study consist of 35 members of Gapoktan Rukun Sentosa who were taken by a saturated sampling technique. The result analysis of this study using SEM PLS showed that self-efficacy, attitude, perceived ease of use, and perceived usefulness influenced the farmers' willingness to adopt the innovation.